Mei Lan-fang’s American Tour and China’s Images in the U.S. (Global Journal of Human-Social Science, 2022)
Since the twentieth century Peking Opera a comprehensive stage art form has been awarded the title of China s national drama and become a well-known cultural symbol of China Mei Lan-fang a female impersonator was reputed to be the most representative actor of Peking Opera In 1930s Mei led a Peking Opera troupe and visited the United States
Keywords: mei lan-fang; peking opera; american images of china